(untitled) (IIUC Business Review, 2026)
Recently, the wave of technology has rolled out across the world. Technology becomes the prime ingredient for future growth and development of the banking services industry. Fintech is the amalgamation of technology based computerized innovation together with financial services intended to enhance the productivity of the financial services industry. This study assesses the impact of fintech income on the financial performance of Islamic banks in Bangladesh. Six Islamic commercial banks are selected as sample and 5 years (2017 to 2021) of data are included. Financial performance of sample Islamic commercial banks is considered as explained variable where return on assets (ROA) and return on equity (ROE) are surrogates for financial performance. Islamic commercial banks generate revenue from diverse fintech based financial services recognized as explanatory variable in this study. The result reveals that fintech income is positively associated with financial performance of sample Islamic commercial banks in Bangladesh. Our study recommends Bangladeshi Islamic commercial banks should enhance investment in fintech products and services for uplifting their financial performance. IIUC Business Review, Vol.-12, Issue-1, December 2023, pp. 75-88